2022
DOI: 10.21037/apm-21-3654
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of different anticoagulation regimens after left atrial appendage occlusion

Abstract: Background: This study examined the safety and efficacy of different anticoagulation regimens in patients with atrial fibrillation (AF) after left atrial appendage occlusion (LAAC) using the Watchman closure device. Methods: AF patients who underwent LAAC using the Watchman closure device in the Department of Cardiology, Jiangsu Taizhou People's Hospital between March 2018 and November 2019 were retrospectively enrolled in this study. Patients were divided into two groups according to different postoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…In conclusion, it was also demonstrated that NOAC + SAPT therapy was safe and effective in short-term follow-up and was associated with lower early DRT formation. 42 …”
Section: The Rationale For Antithrombotic Therapymentioning
confidence: 99%
“…In conclusion, it was also demonstrated that NOAC + SAPT therapy was safe and effective in short-term follow-up and was associated with lower early DRT formation. 42 …”
Section: The Rationale For Antithrombotic Therapymentioning
confidence: 99%
“…Это может указывать на роль сохраняющегося тромбообразования в левых отделах сердца на фоне приема антикоагулянтов у части больных [4]. Основным источником эмбологенных тромбов при нФП (>90% случаев) является левое предсердии (ЛП) и/или его ушко (уЛП) [5]. В среднем, часто-та тромбоза ЛП/уЛП у больных с ФП составляет ~3%, несмотря на использование антикоагулянтов [6].…”
Section: Introductionunclassified